ARTIFICIAL INTELLIGENCE (AI) IN THE LEGAL PROFESSION: EUROPEAN APPROACH (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Latest digital breakthroughs and innovations are shaping the future of artificial intelligence (AI), delving into cutting-edge research, emerging trends and transformative applications across various sectors of human life and national political economies. From deep learning and natural language processing to robotics and autonomous systems, the AI is revolutionizing business models, driving efficiency, unlocking new possibilities and modernizing legal profession. The paper presents a first of its kind attempt in academic and scientific literature to evaluate modern challenges in the digital transformation of lawyers’ work. Hence, the article covers not only elaborated theory and analytical method, but includes literature review concerning modern digital challenges, as well as the state-of-art of modern facilities in emerging AI implications for the legal profession, and the digital transition applicable for the increasing EU’s legal regulations in the European integration. Among the main results of the authors’ research efforts are: e.g. suggestions to introduce new law sectors in national legal classification and orienting the legal profession towards modern challenges and digital transition. The lack of adequate legal specialists in the new spheres of reformed political economies, qualified in using numerous digital technologies and AIs, require additional efforts in legal training and reskilling.